Durkheiḿs Latent Theory of Gender and Homicide - DiCristina, Bruce (The British journal of criminology, 2006)
Emile Durkheim usually neglected gender differences in his discussions of law, punishment and crime, but he did provide a few noteworthy comments on the relationship between gender and homicide. He argued that women commit more intentional homicides than is commonly acknowledged, and he offered a partial explanation of why women, nonetheless, tend to commit fewer homicides than men. In this article, I examine Durkheim's comments on the gender/homicide relationship and explore the conservatism' of his viewpoint on gender. While some of his comments certainly are controversial and empirically questionable, they are significant in that they provide greater insight into early criminological thought on gender and crime. They also help clarify the scope and content of Durkheim's overall criminological perspective. Among other things, they indicate that the variables of gender and opportunity have a noteworthy place within his perspective, and that the importance he attributes to anomie as a causal factor has been exaggerated by the literature of criminology